Democracy in Europe : Legitimising Politics in a Non-State Polity. - Abromeit, Heidrun (Berghahn Books, 1998)
Since the beginning of the European Community students of international politics and of international, resp. Constitutional law, have been wondering what kind of animal it is, and will be, once integration has been completed. Whereas the EC Treaty of 1957 stressed the economic aspects and envisioned a steady and dynamic progress towards a Single Market, it was conspicuously silent about the political implications of integration and the new democratic order. What is needed, so the author argues in this powerful and original contribution to the debate on democratisation of the European Union, i.